2016
DOI: 10.1002/joe.21713
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Innovation in Microfirms to Overcome Resistance to Change

Abstract: For a variety of reasons, strategic innovation in a microfirm's business model can be particularly challenging. One French company that specializes in the distribution of legal announcements and local economic news managed to use IT to not only reinvent its business model but also transform the rules of competition in its sector. Its experiences highlight the particular difficulties that small firms encounter when introducing new technology and the importance of training and creative alliances to ease both int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The current research contributes to bridge the gap regarding resistance to change in the financial management of family firms (Dent and Goldberg, 1999; Broadbent et al , 2001; Frankfurter and McGoun, 2002; Howcroft, 2006; Fritsch and Kublina, 2019). While most of the existing literature focusses on organizational change (Macrì et al , 2002), resistance to change in leadership (Kan and Parry, 2004) and strategic innovation (Bourdon and Jaouen, 2016), it has not been addressed in family firm research (Erwin and Garman, 2010; Pereira et al , 2019). Such studies indicate that organizations are dealing with change, but they have not produced a grounded concept for the rational drivers of resistance to change in family firms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current research contributes to bridge the gap regarding resistance to change in the financial management of family firms (Dent and Goldberg, 1999; Broadbent et al , 2001; Frankfurter and McGoun, 2002; Howcroft, 2006; Fritsch and Kublina, 2019). While most of the existing literature focusses on organizational change (Macrì et al , 2002), resistance to change in leadership (Kan and Parry, 2004) and strategic innovation (Bourdon and Jaouen, 2016), it has not been addressed in family firm research (Erwin and Garman, 2010; Pereira et al , 2019). Such studies indicate that organizations are dealing with change, but they have not produced a grounded concept for the rational drivers of resistance to change in family firms.…”
Section: Discussionmentioning
confidence: 99%
“…In one relatively early study, Handler and Kram (1988) and Gray (2002) conceptualized that resistance to change was linked to firms’ behavioural, cognitive and affective resistance. Existing theories of resistance to change make different assumptions with regard to their preference between change-driving and change-resisting forces in financial management (Erwin and Garman, 2010; Bourdon and Jaouen, 2016; Amarantou et al , 2018). Previous literature reviews demonstrated resistance to change primarily from a managerial viewpoint, in seeing potentially useful rational drivers of change rather than change-resisting forces at a family firm level (Kan and Parry, 2004; Howcroft, 2006; Oreg, 2018).…”
Section: Theoretical Groundingmentioning
confidence: 99%
See 2 more Smart Citations
“…SMEs' employees may also resist changes imposed by new technology due to a lack of specific technical knowledge, difficulty adapting, fear of job loss, or loss of recognition/responsibilities (Birkel et al 2019). According to Bourdon and Jaouen (2016), changing employees' resistance can be easily managed in large companies, but in SMEs, there is a magnification effect; the relative impact of an individual is multiplied (one employee out of ten means that 10% of workforce resists change). The employees may also not be committed to change due to additional workloads required, as reported by one of the case studies of Teoh et al (2022) of an SME that adopted digital BMI.…”
Section: Short Term Visionmentioning
confidence: 99%